A convenção sobre os direitos das pessoas com deficiência e o conceito de capacidade legal: uma comparação entre os sistemas jurídicos do Brasil e de Portugal - Luíza Resende Guimarães (2021)
The International Convention on the Rights of Persons with Disabilies has brought with it paradigmatic changes regarding the legal approach to disability. It was adopted a biopsychosocial view of this phenomenon and stipulated the creation of a system aimed primarily on supporting the exercise of legal capacity – instead of the one based on substituted decision-making –, it imposed a number of challenges on the signatory countries. That said, the main goal of the presente work is to understand if the guidelines on legal capacity provided in artigo 12 of the CRPD have been transposed to the domestic systems of Brazil and Portugal in adequate manner. To accomplish this will, it starts from the concept of material equality, given that legal capacity was guaranteed to people with disabilityes “on equal basis with others”. The investigation is interdisciplinary, which is related to the adoption of the comparative law method, as the research migrates from the strict legal field to reach social and historical spaces that influence the legal system. Interdisciplinarity is salso presente between civil law and constitutional law, since material equality is a concept related to human rights. In addition, there are philosophical interferences, especially regarding the concept of autonomy. The research has a juridical-dogmatic bias and belongs to the juridical-theoretical aspect, revealing its comparative-juridical character in the analysis of the Brazilian and Portuguese legal systems. Also regarding the methodology, the comparative law method will be adopted from its functional perspective, which seeks, in different legal systems, institutes that fulfill the same function, that is, that respond to the same problem. In this particular case, it is about figures aimed to enable decion-making with legal effects from persons with disabilities. Chapter 1 of the dissertation focuses on the general aspects of the CRPD and on the main theoretical models used throughout history to define disability. Chapter 2 intends to investigate the concept of autonomy, focused on its relational approach. Chapter 3 seeks to unravel the meaning and scope of the legal capacity recognized in article 12 of the CRPD, and the analysis culminates in the controversy about the possibility or not to maintain substituted decision-making mechanisms under the aegis of the international document. Finally, the comparison between Brazilian and Portuguese legal systems takes place in Chapter 4, and the objective is to understand to which extent both countries have adapted (or not) to the guidelines drawn up by article 12 of the CRPD. At the end of the research, it appears that both Brazil and Portugal have problems in transposing article 12 to their respective regulations, which in some cases result in lack of protection; and, in others, in veiled maintenance of the status quo.